Church schools, educational markets and the rural idyll. Issue 4 (19th May 2018) - Hemming, Peter J.; Roberts, Christopher
Abstract: Researchers have begun to explore the role that faith schools play in contemporary educational markets but the emphasis to date has been on urban rather than rural contexts. This article approaches the issue of marketisation through a qualitative case-study comparison of two Anglican primary schools in contrasting rural localities in England and Wales. Engaging with a range of stakeholders, including parents and pupils, the article explores reasons why the schools were valued, drawing on wider constructions of childhood, religion and rurality. The consequences of the schools' popularity on factors such as traffic, parking, school ethos and local community ties are also considered. The findings of the study problematise some of the prevalent assumptions about marketisation, including the role of social class and geography in these processes. As such, the article makes an important contribution to the sociological literature on faith schools, rural schools and educational markets.